Green infrastructure drainage of a commercial plaza without directly connected impervious areas: a case study. (21st November 2022) - Rujner, Hendrik; Leonhardt, Günther; Flanagan, Kelsey; Marsalek, Jiri; Viklander, Maria
Abstract: A paired-catchment study of two adjacent commercial areas in northern Sweden, one with Green Infrastructure (GI) storm drainage and the other with a conventional storm sewer system, served to evaluate the hydrological performance of both drainage systems and demonstrate advantages of GI. The GI catchment avoided directly connected impervious areas by diverting runoff from a parking lot to a cascade of three infiltration features, a fractured rock strip draining onto a sloping infiltration area, followed by a collector swale. Both catchments were monitored over 4 years by measuring rainfall, runoff and, in the vicinity of the swale, soil water content and groundwater levels. For frequent storms, the median GI efficiencies in reducing runoff volumes and peak flows, and extending peak flow lags, were 96, 99 and 60%, respectively, compared to conventional drainage. The storm rainfall depth, initial soil water content, increases in intra-event soil water storage and groundwater levels had statistically significant effects on either runoff volume or peak flow reductions. No effects were found for storm rainfall intensity and duration, antecedent dry days, and initial groundwater levels. The study demonstrated that GI drainage can be successfully applied even in the challenging environment of a subarctic climate. HIGHLIGHTS: The hydrology of Green Infrastructure and conventional DCIA drainage was monitored over 5 years. The GI significantly reduced runoff volumes, peak flows and increased lag times compared to conventional drainage. Initial soil water content, increases in intra-event soil water storage, and groundwater levels near the swale affected runoff reductions.